2005
DOI: 10.1111/j.1742-7843.2005.pto_14.x
|View full text |Cite
|
Sign up to set email alerts
|

Aloe Emodin-Induced Apoptosis in t-HSC/Cl-6 Cells Involves a Mitochondria-Mediated Pathway

Abstract: The aim of our study was to clarify the apoptosis pathway induced by aloe emodin, an hydroxyanthraquinone present in aloe vera leaves, in rat hepatic stellate cells transformed by simian virus 40 (t-HSC/Cl-6), which retain the features of activated rat stellate cells. Apoptosis was determined by DNA fragmentation, caspase activity assay and western blotting analysis. Treatment of t-HSC/Cl-6 cells with 12.5, 25, or 50 mM aloe emodin inhibited t-HSC/Cl-6 cell viability in a dose-and time-dependent manner. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…AE has also been reported to have antitumor activity by inducing the arrest of cell cycle in HL-60 cells 1 and apoptosis in T24 human bladder cancer cells, 2 t-HSC/Cl-6 cells, 3 and human lung non-small cell carcinoma cells. 4 However, to our knowledge, there is no available information about the effect of AE on metastasis in human carcinoma cells in vitro.…”
Section: Introductionmentioning
confidence: 97%
“…AE has also been reported to have antitumor activity by inducing the arrest of cell cycle in HL-60 cells 1 and apoptosis in T24 human bladder cancer cells, 2 t-HSC/Cl-6 cells, 3 and human lung non-small cell carcinoma cells. 4 However, to our knowledge, there is no available information about the effect of AE on metastasis in human carcinoma cells in vitro.…”
Section: Introductionmentioning
confidence: 97%
“…Mitochondria play a critical role in the intrinsic pathway by releasing a series of molecules, including cytochrome c. Within the cytosol, the binding of cytochrome c to adaptor protein Apaf-1 and pro-caspasse-9 molecules leads to the formation of the apoptosome that is responsible for activation of a caspase-dependent apoptotic pathway [24]. It has e.g., been reported that emodin-induced apoptosis in rat hepatic stellate cells transformed by simian virus 40 (t-HSC/ Cl-6) involves a mitochondria-mediated pathway [25].…”
Section: Introductionmentioning
confidence: 99%
“…AE has been shown to induce DNA damage through generation of ROS in human lung carcinoma cells (Lee et al, 2006). Studies have also suggested that AE could induce apoptosis via interruption of cell proliferation (Lian et al, 2005).…”
Section: Introductionmentioning
confidence: 99%